Assessment of Secular Trends and Health Risk in Pediatric Cardiorespiratory Fitness From the Republic of Slovenia - Morrison, Shawnda A.; Sember, Vedrana; Leskošek, Bojan; Kovač, Marjeta; Jurak, Gregor; Starc, Gregor (Frontiers in Physiology, 2021)
Objectives Determine the temporal trends in cardiorespiratory fitness (CRF) and health risk of Slovenian schoolchildren across a 20-year span, assessed via 20-m shuttle run (20mSRT), including defining centile ranges and possible health risk(s) for each generation. Methods Nationally-representative data from 9,426 healthy schoolchildren (7-14 years old) were used to determine changes in CRF across three generations, in 1993 (n=3,174), 2003 (n=3,457) and 2013 (n=2,795) from a multistage, stratified, decennial study. Results 20mSRT performance declined ~2.8% from 1993 to 2003, independent of age or sex of the child. This trend was reversed in 2013, increasing by ~8.2% across all age groups, for both girls and boys, for a net increase of 5.4%. The magnitude of improvement was similar for both sexes. Moreover, girls in the 2013 generation (for ages 10-13 y) completed more stages than their 2003 male counterparts. Across all generations, children achieved CRF values corresponding to low cardiovascular risk for future health outcomes. Centile values ranged from ‘low’ to ‘very high’ depending on age, sex and generation of the sample. Conclusion Negative trends in CRF from Slovenian schoolchildren were reversed by 2013, indicating that Slovenia should continue implementing progressive national physical fitness strategies introduced between sampling periods (i.e. 2003‒2013). Additionally, due to the universal nature of Slovenian schoolchildren achieving ‘healthy cut-off values’ for 20mSRT (generation-inclusive), it is suggested that more specific cut-off criteria are developed, especially for younger children, and girls, so that future CRF results can be more accurately applied for both clinical and pedagogical users.